2016
DOI: 10.1016/j.heliyon.2016.e00147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the immunogenicity of an intranasal vaccine against nicotine in mice using the Adjuvant Finlay Proteoliposome (AFPL1)

Abstract: Tobacco smoking is recognized as a global pandemic resulting in 6 million deaths per year. Despite a variety of anti-smoking products available to aid with tobacco cessation, the majority of people who attempt to quit smoking relapse within 6 months due to the addictive nature of nicotine. An immunotherapy approach could offer a promising treatment option by inducing a potent selective antibody response against nicotine in order to block its distribution to the brain and its addictive effects in the central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The World Health Organization estimates that up to half of all lifetime smokers of tobacco will die as a result of smoking; therefore, developing a novel and effective anti-nicotine vaccine is crucial. We previously published the AFPL1-conjugate nicotine vaccine, demonstrating that it is able to bind to nicotine and prevent it from entering the brain in a mouse model [4]. To the best of our knowledge, we were the first group to report a nicotine vaccine that induced both mucosal (IgA, IgG) and systemic anti-nicotine antibodies [5] with no preliminary signs of toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The World Health Organization estimates that up to half of all lifetime smokers of tobacco will die as a result of smoking; therefore, developing a novel and effective anti-nicotine vaccine is crucial. We previously published the AFPL1-conjugate nicotine vaccine, demonstrating that it is able to bind to nicotine and prevent it from entering the brain in a mouse model [4]. To the best of our knowledge, we were the first group to report a nicotine vaccine that induced both mucosal (IgA, IgG) and systemic anti-nicotine antibodies [5] with no preliminary signs of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of the mouse model for the AFPL1-conjugate nicotine vaccine have demonstrated that the vaccine induces anti-nicotine antibodies [4,5]. However, these models use inbred mice, which represents a limitation for assessing heterogeneic responses that would be expected during preclinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations